Situational analysis of stigma associated with HIV/AIDS : a pilot project - Molefe, Aubrey Thabo (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MPhil (Industrial Psychology))--University of Stellenbosch, 2009.